The U.S. Energy System and the Production of Sustainable Aviation Fuel From Clean Electricity - Male, Jonathan L.; Kintner-Meyer, Michael C. W.; Weber, Robert S. (Frontiers in Energy Research, 2021)
Jet fuel is relatively small in terms of energy consumption and carbon dioxide emissions (10% of U.S. transportation sector in 2021, expected to increase to 14% by 2050). Still airlines have ambitious goals to reduce their greenhouse footprints from carbon-neutral growth beginning this year to reducing greenhouse gas emission for international flights by 50% by 2050 compared to 2005 levels. The challenge is heightened by the longevity of the current fleet (30–50 years) and by the difficulty in electrifying the future fleet because only 5% of the commercial aviation greenhouse gas footprint is from regional flights that might, conceivably be electrified using foreseeable technology. Therefore, large amounts of sustainable aviation fuel will be needed to reach the aggressive targets set by airlines. Only 3 million gallons (11.4 ML) of sustainable aviation fuel (SAF) (with a heat of combustion totaling about 400 TJ = 0.0004 EJ) was produced in the U.S. in 2019 for a 26 billion gallon per year market (3.6 EJ/year). Fischer-Tropsch and ethanol oligomerization (alcohol-to-jet) are considered for producing SAF, including the use of renewable electricity and carbon dioxide. In sequencing the energy transition, cleaning the U.S. grid is an important first step to have the largest greenhouse gas emissions reduction. While carbon dioxide and clean electricity can potentially provide the SAF in the future, an ethanol oligomerization option will require less energy.